Small Scale Industries In UP: Marketing Strategies: Exploring the Marketing Strategies of Small Scale Industries in UP (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Marketing is very essential though strenuous, in developing countries like India. The importance of Small Scale Industries (SSIs) is such that their development is concomitant with the balanced growth of Indian economy. Small, Medium or Large scale industries prospects depend upon how well they market their products in the dynamic competitive markets. So with the importance of marketing management in small scale industries increasing and sell the products effectively in the markets. In other words, effective marketing of small scale industrial products would ensure higher levels of income, consumption, and employment which increase the standard of living of the people. Marketing is demanding greater attention not only from industrialists especially of the small scale sector but also from our planners and economists. This empirical study covers the socio-economic conditions, marketing strategies of SSIs and identifies the marketing problems of SSIs. The aim of this is to generate the awareness to the SSIs regarding the blind spots in marketing of their products.